Programmed cell death during retinal development of the mouse eye - Braunger, Barbara M.; Demmer, Cora; Tamm, Ernst R. (Springer New York LLC, 2014)
Similar to other parts of the central nervous system, there are two types of programmed cell death during retinal development. In early development, the neuronal progenitor population is affected. In the mouse eye, this kind of programmed cell death begins at around embryonic day (E) 12.5 and peaks between E14.5 and E16.5. The second phase of programmed cell death occurs during synaptogenesis within the first 2 postnatal weeks. Important signaling mechanisms that induce programmed cell death of retinal progenitors appear to involve nerve growth factor acting on the proapoptotic receptor to p75 neurotrophin receptor (p75NTR) and transforming growth factor-β.
CRIS-Team Scopus Importer:2023-04-11
Keywords: Apoptosis; Neuronal development; Programmed cell death; Retina